Pengaruh Insentif Terhadap Kepuasa Kerja Karyawan Pemadam Kebakaran Aceh Timur - amiruddin, amiruddin (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2022)
This research was conducted at the East Aceh Fire Department with 70 employees as samples. The results of distributing the questionnaires to the sample are used as primary data, then the results of the questionnaire are tabulated, then analyzed using simple linear regression equipment, and testing is carried out by testing the hypothesis t test, testing the correlation coefficient and testing the coefficient of determination. Incentives are additional remuneration received for certain employees whose achievements are above the standard performance. While Job Satisfaction job satisfaction is a feeling that supports or does not support the employee himself related to his work or with his condition. Based on the results of simple linear regression, Y = 5.979 + 0.747X. A constant of 5.979 is the value of the Incentive variable when the Job Satisfaction variable is zero, or if the Incentive variable value is increased by 1 then the Job Satisfaction variable value increases by 5.979. While the value of the correlation coefficient (R) is 0.784 which means the relationship between variables is strong, and the value of the coefficient of determination (R2) is 0.615 indicating that the Incentive variable can affect the Job Satisfaction variable by 0.615 or 61.5% and the remaining 38.5% is influenced by the variable others that were not examined in this study. Then the results of hypothesis testing (t test) obtained tcount > ttable or 10.419 > 1.994 and tsig <5% or 0.00 <0.05 which can be stated that incentives affect job satisfaction of East Aceh Fire Department employees. Keywords: Incentives, Job Satisfaction